PENGARUH PEMAKAIAN KSP DAN UNSUR MIKRO TERHADAP KETERSEDIAAN DAN SERAPAN HARA P (Glycine Max (L) Merr) PADA HISTOSOL DAN ULTISOL - Yulinar Zubaidah; Burhanudin Burhanudin; Irma Yessi (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2006)
The experiment was carried out in greenhouse and in soil laboratory Faculty of Agriculture Andalas University, as well as in Bukittinggi soil laboratory since November 1999 until April 2000. The experiment was designed in Completely Randomized Design in a factorial with 3 replications. The treatments were the KSP dosage (with out KSP, 1500, 2500 and 3500 kg KSP/ha) and micro nutrient (with out micro nutrient, 30 PPM CII S0451120/ha, ;30 ppm Cu. S045H20/ha + 10 ppm ZnS047H20/ha and 30 PPM CU S04H20/ha + 10 ppm S0471120/ha + 0,5 ppm (NH4)6 M024 4H201ha. The results of the experiment showed that application of KSP and micro nutrient combination did not give significant effect on phosphorus available and phosphorus uptake by plants. Application of 2,5 tonnes KSP/ha without application of micronutrient gave the best result to increase soil pH (4,27), P potensial (451,72 ppm), and plan dry weight (16,689/pot) Key words: KSP, Histosol, Ultisol